2008
DOI: 10.1158/1541-7786.mcr-07-0117
|View full text |Cite
|
Sign up to set email alerts
|

CXCL12/CXCR4 Transactivates HER2 in Lipid Rafts of Prostate Cancer Cells and Promotes Growth of Metastatic Deposits in Bone

Abstract: Chemokines and their receptors function in migration and homing of cells to target tissues. Recent evidence suggests that cancer cells use a chemokine receptor axis for metastasis formation at secondary sites. Previously, we showed that binding of the chemokine CXCL12 to its receptor CXCR4 mediated signaling events resulting in matrix metalloproteinase-9 expression in prostate cancer bone metastasis. A variety of methods, including lipid raft isolation, stable overexpression of CXCR4, cellular adhesion, invasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
102
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(107 citation statements)
references
References 49 publications
3
102
0
Order By: Relevance
“…The interaction between SdF-1 and cXcr4 activates the specific signaling pathway controlling homing and metastasis. cXcr4 overexpression was found to enhance bladder tumor growth (17). in addition, cXcr4 may enhance invasive signals and metastatic growth in the bladder microenvironment.…”
Section: Discussionmentioning
confidence: 94%
“…The interaction between SdF-1 and cXcr4 activates the specific signaling pathway controlling homing and metastasis. cXcr4 overexpression was found to enhance bladder tumor growth (17). in addition, cXcr4 may enhance invasive signals and metastatic growth in the bladder microenvironment.…”
Section: Discussionmentioning
confidence: 94%
“…Because several reports demonstrated that activated CXCR4 interacts with signaling factors in lipid rafts, 30,31 we investigated the localization of CXCR4 and Lyn in KBM-5 cells by immunoblot analysis of the individual cellular fractions separated by sucrose gradient ( Figure 2). As the marker of lipid rafts, we used the lipid raft-associated protein flotillin-1.…”
Section: Effects Of Imatinib On Cxcr4 and Lyn Distribution In Lipid Rmentioning
confidence: 99%
“…The activation of FAK and Akt has been reported to be closely associated with cell proliferation, anoikis resistance, migration, invasion and stemness of PC cells. [27][28][29][30][31][40][41][42] CXCR4 leads to the activation of diverse intracellular signaling pathways including the Akt pathway, 34,43,44 and CXCL12 evoked increased expression of FAK and enhanced FAK phosphorylation. 35 Furthermore, it has been established that the tumorigenic and metastatic process of PC is regulated by CXCL12/CXCR4 axis.…”
Section: Discussionmentioning
confidence: 99%